The Effect Of Incentives, Workload And Geographics On The Performance Of Covid-19 Vaccinators North Barito Regency Central Kalimantan - Basirun, Basirun; Ibnu Al Saudi (Sean Institute, 2022)
This study aims to determine whether incentives, workload and geography have a significant effect simultaneously and/or partially and which of the independent variables has the most dominant effect on the performance of Covid-19 vaccinators. The scope of the study was Muara Teweh Regional Hospital and 17 health centers throughout North Barito Regency. Data analysis includes descriptive analysis, classical assumption test, multiple linear regression analysis test, F test, t test, and R2. The results of the study indicate that: 1) Incentives have a positive and significant effect on the performance of Covid-19 vaccinators; 2) Workload has a positive and significant effect on the performance of Covid-19 vaccinators; 3) Geography has a positive and significant effect on the performance of Covid-19 vaccinators; 4) There is a simultaneous influence between Incentives, workload and Geography on the performance of Covid-19 vaccinators with an F-count value of 30.381 and a significance value of 0.000; 5) The Incentive variable is the most dominant variable on Vaccinator Performance with the largest β (Beta) coefficient value, namely 0.474.